Evaluating Factors That Influence Patient Satisfaction in Otolaryngology Clinics. (January 2023) - Redding, Taylor S.; Keefe, Katherine R.; Stephens, Andrew R.; Gurgel, Richard K.
Objectives: To identify factors that influence patient satisfaction during outpatient visits in various settings of otolaryngology clinics in an academic medical center. Study design: Retrospective review. Setting: Academic medical center. Methods: We reviewed Press Ganey patient satisfaction survey responses for new, outpatient visits between January 1, 2014 and December 31, 2018. Self-reported race was identified using electronic medical records. Multivariate binary logistic regression analyses were used to identify continuous and categorical variables associated with patient satisfaction. Results: There were 3998 unique new patient visits with completed surveys. Multivariate analysis revealed that responses for patients <18 years old are less likely to be satisfied with their care compared to patients ≥18 years old (OR 0.66; P  < .001). For each 10-minute increase in wait time, patients were 43.4% less likely report satisfaction ( P  < .001). African American patients were also less likely to report satisfaction (OR 0.22; P  = .043) while Native Hawaiian and Pacific Islanders were over 3 times more likely to be satisfied (OR 3.6; P  = .013). Additionally, Medicare patients and those who were seen at community satellite clinics compared to the main University Hospital had increased odds of achieving satisfactory care (OR 1.3; P  = .005 and OR 1.3; P  = .002, respectively). Conclusions: Wait time, clinic location, patient race, insurance provider, and age were all shown to significantly influence patient-reported satisfaction. Understanding how these variables influence patient satisfaction will hopefully lead to processes that improve patient satisfaction. Level of evidence: Level 3.